REVIEW: THE ROLE OF VITAMIN D SUPPLEMENTATION IN REDUCING THE RISK OF ALZHEIMER'S IN ELDERLY PATIENTS - Saraswati , Dewa Ayu Embas; Kaniawati , Marita; Elva, Deki Riva; Ramadani , Suci (Antis-Publisher, 2024)
Global challenges are increasing as the prevalence of dementia increases. Dementia is considered a multifactorial disease. Dementia is a general term used to describe a range of symptoms that affect memory, thinking and the ability to perform daily activities. Alzheimer's is one of the most common types of dementia, accounting for 75% of all dementia cases. The method used in this article review is the contrast method. The contrast method is a journal/article review method by looking for differences between several research journals and then drawing conclusions. The results showed that alzheimer's is a growing health problem worldwide. The disease burdens the individual as well as the patient's family, which negatively affects the quality of life related to memory and cognitive function. Memory decline or dementia is most common in older people, caused by Alzheimer's disease. . The study concluded that vitamin D supplementation has the potential to reduce the risk of Alzheimer's in elderly patients. Vitamin D is known to play an important role in brain development and function, as well as cognition. Several studies have shown that vitamin D deficiency may increase the risk of cognitive impairment and Alzheimer's, while vitamin D supplementation may improve cognitive function and reduce beta-amyloid accumulation in the brain. However, the results are mixed and limitations remain, so further studies with better designs and larger samples are needed to confirm these findings and understand the underlying biological mechanisms